Platformization, performative perfectionism, and creative stress among local independent musicians in Purwokerto - Mirzani Ahmad; Iin Dyah Indrawati; Madenta Tengger Putra Santoso (Institute of Computer Science (IOCS), 2026)
Digital platforms have transformed music production, promotion, distribution, and audience engagement, but their effects on local independent musicians remain underexplored. Previous studies have discussed platformization, digital music labor, perfectionism, music performance anxiety, royalties, and musicians’ wellbeing separately. However, limited attention has been given to how platform-based visibility, content demands, cover culture, royalty uncertainty, and audience evaluation jointly reshape musical quality, performative perfectionism, and creative stress in local music ecosystems. This study examines how local independent musicians in Purwokerto negotiate platformization, artistic ideals, cover culture, royalties, performative perfectionism, and creative stress. Using a qualitative collective instrumental case study, data were collected through semi-structured interviews with three information-rich cases: Denny Alvian, Polkadots, and Aga/Hyndia. The data were analyzed thematically through the framework of platformization of cultural production. The findings show that digital platforms do not merely distribute songs; they reshape how songs are created, evaluated, promoted, and sustained. Musical quality is increasingly associated with hooks, short-form visibility, engagement, fanbase strength, content adaptability, and algorithmic circulation. Musicians negotiate platform demands while maintaining artistic identity and offline performance opportunities. Cover culture and royalties are interpreted as promotional opportunities, recognition mechanisms, and sources of economic uncertainty. Performative perfectionism emerges when musicians pursue artistic excellence, platform-oriented visibility, and audience approval. These pressures contribute to creative stress when intensive creative work does not produce predictable audience response, monetization, or stage opportunities. This study contributes to digital creative labor and music studies by showing how platformization transforms quality, recognition, perfection, and psychological pressure in a local independent music ecosystem